You made a fool of death with your beauty : a novel - Emezi, Akwaeke (Atria Books, 2022)
"Feyi Adekola wants to learn how to be alive again. It's been five years since the accident that killed the love of her life and she's almost a new person now-an artist with her own studio, and sharing a brownstone apartment with her ride-or-die best friend, Joy, who insists it's time for Feyi to ease back into the dating scene. Feyi isn't ready for anything serious, but a steamy encounter at a rooftop party cascades into a whirlwind summer she could have never imagined: a luxury trip to a tropical island, decadent meals in the glamorous home of a celebrity chef, and a major curator who wants to launch her art career. She's even started dating the perfect guy, but their new relationship might be sabotaged before it has a chance by the dangerous thrill Feyi feels every time she locks eyes with the one person in the house who is most definitely off-limits. This new life she asked for just got a lot more complicated, and Feyi must begin her search for real answers. Who is she ready to become? Can she release her past and honor her grief while still embracing her future? And, of course, there's the biggest question of all-how far is she willing to go for a second chance at love? Akwaeke Emezi's vivid and passionate writing takes us deep into a world of possibility and healing, and the constant bravery of choosing love against all odds"--